THE RELATIONSHIP BETWEEN SERUM SUBSTANCE P LEVELS AND ACNE VULGARIS - Ika Syani Putri Lubis (Journal of Public Health Science, 2026)
This study aims to analyze the relationship between serum substance P levels and acne vulgaris using the Chi-square test. This is an observational analytical study with a case-control approach. Sampling was conducted at the Cosmetic Division Polyclinic of KSM Dermatology and Venereology. The sample size for this study is 30 acne vulgaris patients and 30 control subjects. Consecutive sampling will be used in this study. The collected data will be analyzed statistically. The study concludes that there is a relationship between serum substance P levels and acne vulgaris. High serum substance P levels associated with of acne vulgaris by 5.4 times. The mean serum substance P level in acne vulgaris is 62.6 ± 32.4 pg/ml. The highest mean serum substance P levels in acne vulgaris are found in the 28-32 year age group. The mean serum substance P levels in acne vulgaris are highest in men by gender.